Types and abundance of phytoplankton of the Boko-Boko Peat swamp in the Langgam Village, Langgam District, Pelalawan Regency, Riau Province - Agung Prabowo; Asmika Harnalin Simarmata; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The area around the Boko-Boko peat swamp has been used for palm plantation. Remains of fertilizer and pestiside used in the plantation may enter the water and decrease the water quality of the swamp and thus reduce the water quality in general. To understand the type and abundance of phytoplankton in the Boko-Boko peat swamp’s waters, a research was conducted in March 2016. There were three sampling stations namely Station 1, Station 2, and Station 3. Samplings were conducted 3 times, once/week. Results shown that there are 18 species of phytoplankton present in the peat swamp. They were classified into four classes, namely: Bacillariophyceae (6 species), Chloropyhceae (1 species), Cyanophyceae (5 species) and Xanthophycea (3 Species). The average of phytoplankton abundance was around 10,948 – 18,186 cells/L, species diversity index (H’) was 2.082 -2.424, index equatibility (E) was 0.81 – 0.86 and dominance index (C) was 0.218 – 0.288. While the water quality parameters were as follows: temperature 30.1 – 30.4 0C, transparency 48.6 - 60 cm, depth 148.3 – 180 cm, pH 5, CO2 : 7.32 – 9.99 mg/L, DO : 2.54 – 3.26 mg/L, nitrate : 0.4444 – 0.6436 mg/L and phosphate : 0.7779 – 0.123 mg/L. Based on the abundance of pyhtoplankton, it can be concluded that the peat swamp Boko - Boko can be categorized as mesotropic.Keywords : Phytoplankton, Peat Swamp, WaterQuality, Boko-Boko